Interchangeability of back extrapolation and exercising oxygen uptake measure during front crawl swimming - Leprêtre, P.; Cassirame, J. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
Oxygen uptake (VO2) measurements are a technical challenge in ecological exercise conditions with face immersion. Backward extrapolation was proposed to estimate swimming VO2 value based on post-exercise VO2 and exercise heart rate values (pVO2(t)). Specific snorkel has been already released to measure VO2 (swim-VO2) in a flume. The study aimed to compare swim-VO2 and pVO2(t) during non-tethered swimming. 10 well-trained swimmers (20.1±4.1y, 176.7±9.2cm, 64.9±12.4kg) performed 4 ´ 200m front crawl at different intensities (moderate to severe) separated by 1-min of passive recovery in water. VO2 was collected using Metamax3B-R3 with Metaswim (Cortex biophysics, Liepzig, Germany). swim-VO2, pVO2(t) and their agreement with each other were determined. No significant difference was found between mean swim-VO2 and pVO2(t) values (3.4±0.7 vs. 3.4±0.8L·min-1, p=0.083). The variation between swim-VO2 and pVO2(t) was -0.9±3.9% (from -6.9 to 9.6%). swim-VO2 and pVO2(t) were significantly correlated (r=0.99 for 95% confidence limits). A good level of agreement was found between two methods [-0.21;0.29] L·min-1. Mean, upper and lower limits of bias were 0.05, 0.20 and -0.07 with a small standardized typical error of estimate (i.e., 0.15). Both methods could be considered as interchangeable for estimating VO2 during front crawl swimming from moderate to severe intensities.